Hydroxyurea Scavenges Free Radicals and Induces the Expression of Antioxidant Genes in Human Cell Cultures Treated With Hemin - Santana, Sânzio Silva; Pitanga, Thassila Nogueira; de Santana, Jeanne Machado; Zanette, Dalila Lucíola; Vieira, Jamile de Jesus; Yahouédéhou, Sètondji Cocou Modeste Alexandre; Adanho, Corynne Stéphanie Ahouefa; Viana, Sayonara de Melo; Luz, Nivea Farias; Borges, Valeria Matos; Goncalves, Marilda Souza (Frontiers in Immunology, 2020)
The excessive release of heme during hemolysis contributes to the severity of sickle cell anemia (SCA) by exacerbating hemoglobin S (HbS) autoxidation, inflammation and systemic tissue damage. The present study investigated the effect of hydroxyurea (HU) on free radical neutralization and its stimulation of antioxidant genes in human peripheral blood mononuclear cells (PBMC) and human umbilical vein endothelial cells (HUVEC) in the presence or absence of hemin. HU (100 and 200 µM) significantly reduced the production of intracellular reactive oxygen species (ROS) induced by hemin at 70 µM in HUVEC. HUVECs treated with HU+hemin presented significant increases in nitric oxide (NO) production in culture supernatants. HU alone or in combination with hemin promoted the induction of superoxide dismutase-1 (SOD1) and glutathione disulfide-reductase (GSR) in HUVECs and PBMCs, and glutathione peroxidase (GPX1) in PBMCs. Microarray analysis performed in HUVECs indicated that HU induces increased expression of genes involved in the antioxidant response system: SOD2, GSR, microsomal glutathione S-transferase (MGST1), glutathione S-transferase mu 2 (GSTM2), carbonyl reductase 1 (CBR1) and klotho B (KLB). Significant increases in expression were observed in genes with kinase activity: protein kinase C beta (PRKCB), zeta (PRKCZ) and phosphatidylinositol-4-phosphate 3-kinase catalytic subunit type 2 beta (PIK3C2B). HU also induced a significant increase in expression of the gene p62/sequestosome (p62/SQSTM1) and a significant decrease in the expression of the transcriptional factor BACH1 in in HUVECs. Upstream analysis predicted the activation of Jun, miR-155-5p and mir-141-3p. These results suggest that HU directly scavenges free radicals and induces the expression of antioxidant genes via induction of the Nrf2 signaling pathway.